Fabrication and Characterization of Photoelectrocatalytic Electrodes of Carbon Nanotube/Titanium Oxide - Oh, Won-Chun; Zhang, Feng-Jun; Chen, Ming-Liang (Asian Journal of Chemistry, 2010)
In this paper, we have prepared three types of carbon nanotube/titanium oxide (CNT/TiO2) electrodes (designated as SCTE1, SCTE2 and SCTE3). The electrodes prepared were characterized by surface properties, structural crystallinity, elemental identification and photoelectrocatalytic activity. Nitrogen adsorption data showed that the composites had decreased surface area compared with pristine CNTs, indicating blocking of micropores on the CNT surfaces, which was further supported by observations via SEM. XRD patterns of the composites showed that the SCTE 1 composite contained only a typical single and clear anatase form while the SCTE2 and SCTE3 contained a mixture of anatase and rutile phases. EDX spectra showed the presence of C, O and Ti peaks for all samples. The catalytic efficiency of the electrodes prepared was evaluated by the photoelectrodegradation of methylene blue. The positive potential applied in photoelectrocatalytic oxidation was studied. It was found that photoelectrocatalytic decomposition of methylene blue could be attributed to the synthesized effects of TiO2 photocatalytic, CNT electro-assisted and as function of applied potential. The efficiency of photoelectrocatalytic oxidation for methylene blue is higher than that of photocatalytic oxidation. A degradation mechanism is presented.